Problems of Participation and Issues of Sustainability in the Public Irrigation System in the Context of Management Transfer: Some Sociological Observations from Eastern Terai, Nepal - Uprety, Laya Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2011)
It has been ascertained that participatory processes did not involve learning component from both agency and water users’ association for institutional and technical sustainability. The overall process of participation was superficial. There was a need of participation that underscored the empowerment of WUA with accountability. As Vermillion (2005) shares that empowerment with partnership is an emergent institutional paradigm for the irrigation sector development that places water users in the role of irrigation system governance, and government in the roles of regulator and provider of support services. There is a need to re-train the irrigation staff on the emergent institutional paradigm to empower the water users. For the empowerment with accountability, water users are to be provided enough institutional strengthening. There is the need to promote user-agency relationship positively and develop faith and confidence of the users and agency in the regime of transparency. Social scientists point out potential benefits of building successful local organizations. These benefits, for the local people, are in aspects such as empowerment, confidence-building, forming social capital, and reduction of dependency. Given the fact that participation is a process, it cannot be achieved in a short span of time with little institutional inputs. Sustainability of the management transferred irrigation systems/sub-systems definitely hinges on the broad-based and inclusive participatory processes. Keywords: participation; sustainability; management transfer; social capital and empowerment DOI: 10.3126/dsaj.v4i0.4512 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.41-64